2012
DOI: 10.1186/1471-2148-12-83
|View full text |Cite
|
Sign up to set email alerts
|

Ancient gene transfer from algae to animals: Mechanisms and evolutionary significance

Abstract: BackgroundHorizontal gene transfer (HGT) is traditionally considered to be rare in multicellular eukaryotes such as animals. Recently, many genes of miscellaneous algal origins were discovered in choanoflagellates. Considering that choanoflagellates are the existing closest relatives of animals, we speculated that ancient HGT might have occurred in the unicellular ancestor of animals and affected the long-term evolution of animals.ResultsThrough genome screening, phylogenetic and domain analyses, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 85 publications
2
29
0
Order By: Relevance
“…These viral and bacterial genes were integrated into mitochondria and passed onto descendants ultimately through the apical meristem. Such observations, combined with other relatively recent HGT events reported in plants1317 and animals161846, suggest that neither germline nor apical meristem constitutes an insurmountable barrier to HGT.…”
Section: Discussionmentioning
confidence: 57%
“…These viral and bacterial genes were integrated into mitochondria and passed onto descendants ultimately through the apical meristem. Such observations, combined with other relatively recent HGT events reported in plants1317 and animals161846, suggest that neither germline nor apical meristem constitutes an insurmountable barrier to HGT.…”
Section: Discussionmentioning
confidence: 57%
“…As Ni et al (46) conclude, "Most identified algal genes (identified by the authors as potential transfers from alga/ cyanobacteria to Ciona intestinalis) are related to molecule transport and signaling, suggesting their important role in intercellular communication and possibly the origin of multicellularity in animals." The fatty acid heme dioxygenases and cyclooxygenases certainly fit into the categories of signaling and intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…As the first heterotrophic (non-phototrophic) multicellular organisms evolved, prokaryotes and protists would have been the fundamental nutrient sources. Choanoflagellates, are thought to be the most closely related protist lineage to the metazoan (King et al, 2008;Ni et al, 2012;Ra, 2012;Tucker, 2013;Tucker et al, 2012). However, considerable controversy exists for the phylogenetic relationships of the basal metazoans.…”
Section: Teneurins and Their Evolutionmentioning
confidence: 97%